The development of signing and verification methods for high speed digital signatures on electronic official documents by using RSA cryptography - Kritsanapong Somsuk (Cogent Engineering)
This research introduces an algorithm for signing and verifying digital signatures on electronic official documents to establish the authenticity of a person’s identification. The proposed method focuses on minimizing processing. The process begins by converting the electronic document into a digital image. The image is converted into a black-and-white format to reduce the quantity of detail. Then, only specific regions containing handwritten data are extracted for processing. In fact, the proposed method effectively chooses and handles only the black pixels in the extracted image parts. Additionally, the verification process utilizes the best equations, including Chinese remainder theorem, to further optimize processing time. The experimental results are separated into two sections. The first phase involves determining the average duration of the entire system using the proposed method, which falls within the range of 33–35 seconds. The second part is the comparison between the proposed method (utilizing data extraction from selected black pixels) and a method processing all pixel data for verification. The result shows that the proposed method demonstrates a substantial reduction in processing time. Furthermore, the proposed method significantly provides reliable identity verification even though only a small portion of the pixel data is extracted.